Buddhism a very short introduction. - Keown, Damien 1951- (Oxford Oxford University Press, 2013)
"Since its origins in India over two thousand years ago, Buddhism has not only spread throughout Asia, but also around the world. In this new edition of the Very Short Introduction to Buddhism, Damien Keown looks at how the tradition began and how it evolved into its present-day form. Explaining its central teachings and practices as well as key topics such as karma and rebirth, meditation and ethics, Keown also includes updates related to the evolution of Buddhism within Asia and the West, the importance of material culture, and the ethics of war and peace."--P. [2] of cover.
Buddhism and elephants -- The Buddha -- Karma and rebirth -- The Four Noble Truths -- The Mahāyāna -- The spread of Buddhism -- Meditation -- Ethics -- Buddhism in the West.
Keywords: Buddhism; 294.3 <036> -- Boeddhisme--(algemeen)--Gidsen. Inleidingen